كتاب "زهر الآداب وثمر الألباب" للحصري القيرواني : دراسة نصية وتحليلية - َّطاهر، زينب محمد النعاس (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to deal with Arabic literary heritage by re-reading the writingon literary heritage and analyzing texts through modern linguistic methods. This study tries to implement these methods on selected texts in the book; “Zahr al-AdabwaThamar al-Albab” written by al-Husri al-Qayrawani. This book has the characteristics of Arabic literary heritage which are products of deep idea, wide knowledge and literarysophiscation. This study applied two aspects of textual linguistics from Robert de Beaugrand: informativity and intentionality in order to implement the modern linguistic methods. The main idea of these methods is analyzing a text by describing it from the linguistic aspect, and it covers all types of texts from various contexts. These modern linguistic methods were applied to selected texts from: “Zahr al-AdabwaThamar al-Albab” by employing descriptive and analytical methods. Themain result of this study shows the texts of al-Husri have hidden and clear meanings and can be concluded under five points. Firstly, revealing the strength of the texts from the speech acts theory such as vocation, authority, prohibition, cautioning, adjuration and interrogative. Second, the message of the texts depends on the second stage of informativity aspect. Third, the texts of al-Husri show the broadening of language such as anastrophe, apostrophe, metonymy, metaphor, intertectuality and polysemy. Fourth, extracting meanings and objectives from prose texts, and finally highlighting the sophistication of Arabic prose texts in literary heritage.